2023
DOI: 10.1039/d2dt02559k
|View full text |Cite
|
Sign up to set email alerts
|

Comparative oxidative ability of mononuclear and dinuclear high-valent iron–oxo species towards the activation of methane: does the axial/bridge atom modulate the reactivity?

Abstract: Over the years, mononuclear FeIV=O species have been extensively studied, but the presence of dinuclear FeIV=O species in soluble methane monooxygenase (sMMO) inspired the development of biomimic models that could...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 144 publications
0
4
0
Order By: Relevance
“…Consistent with experimental and theoretical data, ,,,, the computed energetics confirm that all Fe(IV)-oxo/hydroxo models have an intermediate spin ( S = 1) ground state, well-separated from either the low or the high spin alternatives (Tables S2 and S3). The ground state prediction is uniformly consistent between DFT and high-level DLPNO-CCSD(T) calculations, with the two approaches differing in the relative ordering of the excited S = 2 and S = 0 states, a topic that is however of no concern here. The calculated spin density plots for all 16 model ground states are shown in Figure S3, and the spin populations are listed in Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with experimental and theoretical data, ,,,, the computed energetics confirm that all Fe(IV)-oxo/hydroxo models have an intermediate spin ( S = 1) ground state, well-separated from either the low or the high spin alternatives (Tables S2 and S3). The ground state prediction is uniformly consistent between DFT and high-level DLPNO-CCSD(T) calculations, with the two approaches differing in the relative ordering of the excited S = 2 and S = 0 states, a topic that is however of no concern here. The calculated spin density plots for all 16 model ground states are shown in Figure S3, and the spin populations are listed in Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the natural bond orbital (NBO) study of the title molecule 3 and 3-CN was computed at the B3LYP/6-31g level of the model. 41 This analysis aimed to elucidate electron density delocalization and intra-and inter-molecular bonding, and explore charge transfer (CT) or the extent of conjugative interaction between the benzithiazolyl and 3-pyrrolyl BODIPY units in compound 3. Second-order perturbation theory, applied to the Fock matrix, was utilized to evaluate donor-acceptor interactions in the NBO investigation.…”
Section: Dft/td-dft Studiesmentioning
confidence: 99%
“…Our hypothesis is supported by the study of arylruthenium(III) porphyrin, which was found to be highly active catalysts for hydrocarbon oxidation [45] . Closely related systems employing Fe cations have also been investigated in context of methane oxidation by Ansari and co‐workers [46,47] . The authors found that the typically high energy barrier for the C−H bond activation can be significantly reduced in the case of Fe binuclear complex, what allows the reaction to occur via the excited intermediate.…”
Section: Introductionmentioning
confidence: 99%